Bioinformatics Approach: Evaluating the Antiviral Potential of Flavonoid Compounds from Phyllanthus urinaria against Foot-and-Mouth Disease in Livestock Animals - Nugroho, Endik Deni; Sururi, Ahmad Misbakhus; Ardiansyah, Reza; Rahayu, Dwi Anggorowati; Ainiyah, Roisatul; Fathurrohman, Amang; Ahwan, Zainul; Dayat, Muhammad; Wibisono, Mulyono; Aji, Fatit Rahmar; Kasiman, Kasiman (ALCHEMY:Journal of Chemistry, 2024)
Foot-and-mouth disease is a severe problem that must be faced in the livestock sector. This disease has a negative impact on various aspects, especially the economy. One way to develop herbal medicinal compounds is through local Indonesian wild plants, meniran (Phyllanthus urinaria). This research aims to determine the potential of the wild plant P. urinaria as an antiviral agent for FMD using an in silico approach using molecular docking. The compounds used as ligands are flavonoid compounds in P. urinaria, namely, routine, quercetin 7-methyl ether, quercetin 3-O-β-D-glucoside, quercetin, rhamnocitrin, astragalin, and kaempferol. This study used the control drug ribavirin as a comparison. The research stage began with the preparation of the RdRp protein from the FMD virus with Discovery Studio, ligand preparation with the Lipinski druglikeness test and minimization using OpenBabel, followed by docking and visualization. The research results found that the six flavonoid compounds in P. urinaria have potential as antiviral FMD by inhibiting RdRp, with the most potent compound being quercetin (-7.9 kcal/mol). Further research is needed, including in vitro and in vivo testing, to provide confidence in the potential of this wild plant as an antiviral for FMD.